Peran Perempuan Rifaiyah Mempertahankan Ajaran Islam Rifa’iyah: Studi Kasus di Pati Jawa Tengah - Moh. Rosyid (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2020)
The purpose of this study is portraying women’s role in maintaining tarekat Rifaiyah. This paper is a qualitative research based on literature, observation and interview among jamaah Rifaiyah in Tambangsari, Kedungwinong, Sukolilo, Pati, Central Java. Rifaiyah is a tarekat based on the teaching of KH Ahmad Rifa’i of Kalisalak. It was introduced to the people of Pati by the grandson of KH Ahmad Rifa’i. Theresult shows that women have played several roles: women religious congregation as well as female preachers in Tambangsari, teaching al-Quran in madrasah and regular meeting to learn the Book of Tarjumah.